Relationships Among Valued Action, Behavioral Activation, Avoidance, and Reinforcement in a Sample of College Students. Issue 1 (February 2016) - Doi, S.; Yokomitsu, K.; Sakano, Y.
Behavioral activation is a validated intervention for depression, which helps depressed people re-engage overt behaviors to facilitate contacts with reinforcing environmental contingencies and subsequent reductions in depression. Moreover, behavioral activation deals with values that are based on acceptance and commitment therapy. However, there is no empirical study that examines the role of behavior in line with values in behavioral activation. This study examined the role of behavior in line with values in behavioral activation by examining the association between behavior in line with values and variables of behavioral activation intervention targets, as well as the mediating effect of behavioral commitment. Japanese versions of the Personal Values Questionnaire II, the Behavioral Activation for Depression Scale, the Environmental Reward Observation Scale, and the Center for Epidemiological Studies Depression were completed by 292 Japanese undergraduate students ( M age = 19.2 yr., SD  = 1.7; 65 men, 226 women, 1 unknown). Results indicated that behavior in line with values was associated with focused, goal-directed activation and completion of scheduled activities, which were mediated by behavioral commitment to values.